2018
DOI: 10.1111/cns.13069
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ferroptosis attenuates tissue damage and improves long‐term outcomes after traumatic brain injury in mice

Abstract: Summary Aims Ferroptosis, a new form of iron‐dependent programmed cell death, has been shown to be involved in a range of diseases. However, the role of ferroptosis in traumatic brain injury (TBI) has yet to be elucidated. We aimed to investigate whether ferroptosis is induced after TBI and whether the inhibition of ferroptosis would protect against traumatic brain injury in a controlled cortical impact injury (CCI) mouse model. Methods After establishing the TBI model in mice, we determined the biochemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
187
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(211 citation statements)
references
References 42 publications
11
187
1
Order By: Relevance
“…In our study, we observed accumulation of MDA and Fe 2+ and alternation of the above-mentioned metabolism-related molecules after CCI. Our findings together with previous reports indicate that ferroptosis is involved in the pathogenesis of CCI [35]. Many of our results are consistent with previous studies [11,35,36], with some exceptions.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study, we observed accumulation of MDA and Fe 2+ and alternation of the above-mentioned metabolism-related molecules after CCI. Our findings together with previous reports indicate that ferroptosis is involved in the pathogenesis of CCI [35]. Many of our results are consistent with previous studies [11,35,36], with some exceptions.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings together with previous reports indicate that ferroptosis is involved in the pathogenesis of CCI [35]. Many of our results are consistent with previous studies [11,35,36], with some exceptions. Gpx4 (converts toxic lipid hydroperoxides to non-toxic lipid alcohols) was reported to decrease after TBI [10], but in our study, its expression was barely changed compared to the sham group at all indicated time points except for the 6 h group in which an increased level of Gpx4 was observed.…”
Section: Discussionsupporting
confidence: 94%
“…The evolution of TBI is accompanied by biological processes, such as iron accumulation, disordered iron metabolism, upregulation of ferroptosis-related genes, decreased GPX activity and ROS accumulation 75 . The application of the ferroptosis inhibitor Fer-1 significantly reduces iron deposition, neuronal degeneration, and injury and improves the prognosis of patients, thus providing an experimental basis for TBI treatment targeting ferroptosis 75 .…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 99%
“…Recently, Do Van B etc. confirmed that ferroptosis was a new way of cell death in Parkinson's disease [25] . Ferroptosis also makes contribution to the neuronal loss in Alzheimer's disease [26] .…”
Section: Ferroptosis Inhibitor Ferrostatin-1 Can Protect Cell Death Imentioning
confidence: 84%